Resposta :
[tex]3x + 9 = x + 3 \\ 3x - x = 3 - 9 \\ 2x = - 6 \\ x = \frac{ - 6}{2} \\ \\ {\boxed{\sf \ \red{x = - 3}}}[/tex]
-----------------------------------------------------------
[tex]4y - 7 = 2y - 3 \\ 4y - 2y = - 3 + 7 \\ 2y = 4 \\ y = \frac{4}{2} \\ \\{\boxed{\sf \ \red{y = 2}}} [/tex]
espero ter ajudado!
Resposta:
Solução:
[tex]\sf \displaystyle 3x +9 = x + 3[/tex]
[tex]\sf \displaystyle[/tex][tex]\sf \displaystyle 3x- x = 3 - 6[/tex]
[tex]\sf \displaystyle 2x = -6[/tex]
[tex]\sf \displaystyle x = -\:\dfrac{6}{2}[/tex]
[tex]\boxed{ \boxed { \boldsymbol{ \sf \displaystyle x = -3}}} \quad \gets \text{\sf \textbf{Resposta } }[/tex]
[tex]\sf \displaystyle 4y - 7= 2y - 3[/tex]
[tex]\sf \displaystyle 4y - 2y = - 3 +7[/tex]
[tex]\sf \displaystyle 2y = 4[/tex]
[tex]\sf \displaystyle y = \dfrac{4}{2}[/tex]
[tex]\boxed{ \boxed { \boldsymbol{ \sf \displaystyle y = 2}}} \quad \gets \text{\sf \textbf{Resposta } }[/tex]
Explicação passo-a-passo: